2017
DOI: 10.1115/1.4036214
|View full text |Cite
|
Sign up to set email alerts
|

General Relations of Indentations on Solids With Surface Tension

Abstract: The conventional contact mechanics does not account for surface tension; however, it is important for micro- or nanosized contacts. In the present paper, the influences of surface tension on the indentations of an elastic half-space by a rigid sphere, cone, and flat-ended cylinder are investigated, and the corresponding singular integral equations are formulated. Due to the complicated structure of the integral kernel, it is difficult to obtain their analytical solutions. By using the Gauss–Chebyshev quadratur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The variations of indentation load and indentation depth with respect to the ratio s/a are plotted in Figures 5A,B, respectively. It is seen that our numerical results obtained from BEM calculations coincide well with existing semi-analytical solutions (Kim and Gouldstone, 2008;Long et al, 2017). The size dependent contact behavior is reproduced.…”
Section: Contact With An Axisymmetric Parabolic Indentersupporting
confidence: 83%
See 2 more Smart Citations
“…The variations of indentation load and indentation depth with respect to the ratio s/a are plotted in Figures 5A,B, respectively. It is seen that our numerical results obtained from BEM calculations coincide well with existing semi-analytical solutions (Kim and Gouldstone, 2008;Long et al, 2017). The size dependent contact behavior is reproduced.…”
Section: Contact With An Axisymmetric Parabolic Indentersupporting
confidence: 83%
“…The constant membrane tension in Hajji (1978) and Kim and Gouldstone (2008) is corresponding to the residual surface tension, and the superficial layer modeled in Argatov and Sabina (2012) and Argatov and Mishuris (2016) can be considered as a solid surface with surface elasticity. Recently, problems of surface loadings and contacts have been widely studied based on the surface elasticity theory (He and Lim, 2006;Wang and Feng, 2007;Zhou and Gao, 2013;Long et al, 2017;. It is found that the deformation behavior would be distinctly different from classical models when the size of loading is comparable or even smaller than a critical length, usually at nano/microscale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herewith, we skip all the details and only present the final solution. Based on the dimension analysis and the numerical results, we can parameterize the load P and the contact radius a in terms of the indent depth δ as (Long et al, 2017) respectively. Thus, in the ST-DMT model, the dependence of load P on the indent depth δ is given by…”
Section: The Dmt Model With Surface Tensionmentioning
confidence: 99%
“…In recent decades, attentions on the influence of surface tension or surface energy on contact problems of elastic materials has grown considerably. Based on the surface Green's functions with surface tension [17,18], Long et al [19,20] analysed the plane strain and axisymmetric contact problems respectively, and suggested that the existence of surface tension could lead to evident size-dependent contact responses.…”
Section: Introductionmentioning
confidence: 99%